Reciprocal Teaching Strategy on Reading Comprehension: A Review for Prospective Teachers - Hasbi, Muhammad; Razaq, Yusuf; Muzkiyah, Nurul; Fahira, Ainun; Satriani, Satriani (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The focus of this research was to use the reciprocal teaching strategy to increase prospective teachers reading comprehension in the sixth semester of English education at IAI As'adiyah Sengkang. A pre-experimental approach with pretest and posttest design was used by the researcher. Using the cluster random sampling technique, a total of 13 people were included in the sample. This study used a 20-item multiple-choice reading test as the research tool. Pre-test and post-test data were obtained. The data analysis revealed that the mean score of prospective teachers pre-tests was 59, 29 and the mean score of prospective teachers post-tests was 77,62. It was discovered that after undergoing reciprocal teaching strategy treatment, the prospective teachers reading comprehension improved (α < 0.05). The researcher found that a reciprocal teaching strategy was appropriate in teaching reading comprehension at IAI As'adiyah Sengkang's sixth semester of English education based on the results of data analysis. Reciprocal teaching strategy can be used as an alternative strategy in the teaching and learning process by English teachers and other scholars.